2023
DOI: 10.1136/bmjgh-2023-012433
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 vaccine uptake among adults in South Africa: multimethod evidence from a population-based longitudinal study

Abstract: BackgroundCOVID-19 vaccine coverage remains low in many low and middle-income countries despite widespread access. To understand the dynamic decision-making process around vaccination and provide evidence for future vaccine promotion campaigns, we identified predictors of COVID-19 vaccine uptake among South African adults, including those who did not believe in the vaccine’s safety or efficacy.MethodsData from two longitudinal telephone surveys in late 2021 and early 2022 of unvaccinated South African adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Among the COVID-19 vaccine associated factors, confidence in vaccine safety and efficacy was associated with better acceptance. Numerous studies have shown that vaccine acceptance was associated with confidence in safety and effectiveness [ 9 , 33 , 34 ]. Concern about vaccine safety remains a ubiquitous barrier, compound by the concern about safety on the developing fetus as found by a previous survey [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the COVID-19 vaccine associated factors, confidence in vaccine safety and efficacy was associated with better acceptance. Numerous studies have shown that vaccine acceptance was associated with confidence in safety and effectiveness [ 9 , 33 , 34 ]. Concern about vaccine safety remains a ubiquitous barrier, compound by the concern about safety on the developing fetus as found by a previous survey [ 17 ].…”
Section: Discussionmentioning
confidence: 99%